2010
DOI: 10.4028/www.scientific.net/ast.70.59
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Shock Behavior of Zircon Based Refractories

Abstract: In service refractory materials are submitted to local temperature gradients that originate thermal stresses causing a thermal shock (TS) damage to the material. Practical tests for evaluating the thermal shock resistance (TSR) determine the variation or change of some characteristic property of the test sample like E (elastic module) or the strength before and after quenching. In this work, the microstructure and thermal shock behavior of Zircon based refractories are analyzed. Several compositions (eight), f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…A number of previous works have confirmed that there is a correlation between the degree of thermal shock damage and the change in flexural strength before and after quenching [13,19,28]. It is somewhat surprising from the above experimental data that the change degree of each material in flexural strength before and after thermal shock test can reflect its ability in the resistance to thermal shock.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…A number of previous works have confirmed that there is a correlation between the degree of thermal shock damage and the change in flexural strength before and after quenching [13,19,28]. It is somewhat surprising from the above experimental data that the change degree of each material in flexural strength before and after thermal shock test can reflect its ability in the resistance to thermal shock.…”
mentioning
confidence: 73%
“…In the past several decades, many strides aiming at the development of theories and methods for evaluating thermal shock resistance of ceramics have been reported [15][16][17][18][19]. However, the approaches currently used in the evaluation of thermal shock resistance are largely based on the research results of  Kingery [15] and Hasselman [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La tabla 3 muestra las propiedades como, contracción lineal de secado (C.S) y contracción en cocción (C.C), densidad aparente (D.A), absorción de agua (A.A), Resistencia a la flexión (R.F), porosidad aparente (P.A) y cono pirométrico equivalente (PCE). Estas propiedades son muy utilizadas en la evaluación y comparación de la calidad del producto, como parte de los criterios de selección y usos de los productos refractarios en variedad de aplicaciones industriales (13,14,15). La menor contracción de secado la presentó el prototipo de la mezcla MA arrojando un valor de 0,1%, y la más alta fue presentada por la mezcla MB siendo 0,34% su valor.…”
Section: Caracterización De Las Materias Primasunclassified
“…Zirconium silicate (ZrSiO 4 ) is an important antioxidant material of non-metallic minerals due to its low expansion coefficient, low oxygen diffusion coefficient and excellent thermal shock resistance. As one of refractory [1], high temperature structural ceramics [2] and anti-oxidation materials [3], it also has a broad application prospect in environmental barrier coating [4] (EBC). Over past few years, ZrSiO 4 films have been prepared by kinds of methods such as atomic layer deposition [5] (ALD) method, chemical vapor deposition [6] (CVD) method, metal organic chemical vapor deposition [7] (MOCVD) method, sputtering [8] method and hydrolytic sol-gel [9] (HSG) method, etc.…”
Section: Introductionmentioning
confidence: 99%